The effect of training provided for obese adolescents based on Health Promotion Model on their healthy lifestyle behaviors and life quality - Yılmaz Yavuz, Ayten; Hacıalioğlu, Nazlı (Progress in Nutrition, 2018)
Objectives: The purpose of this study is to determine the effect of training provided for obese adolescents based on health promotion model on their healthy lifestyle behaviors and life quality. Methods: The research was conducted on the 114 obese adolescents in the form of intervention design with pretest- posttest control group between the dates September 2012 and January 2014. The experiment group was trained for three months within the Health Promotion Model which was constituted to decrease the risk factors of obesity. Results: With the training, monitoring and consultancy service provided for obese adolescents, it was found that BMI scores decreased significantly, their nutritional and physical activity habits were regulated, their sedentary life decreased, their general score averages for ALP and PedsQL scale were higher when compared with the pre-test and the difference between the experiment and control groups was found to be statistically significant (p<0.05). Conclusion: It was determined that the training obese students received which was based on health promotion model helped the students to develop healthy life style behaviors and to increase their life quality.